The Impact of Demographic and Individual Heterogeneity on Unemployment Duration: A Regional Study - William Collier (European Regional Science Association (ERSA), 2003)
Since 1992, claimant unemployment has fallen by almost 1 million and on the ILO definition by nearly 1 million. Despite this fall, changes to the headline rate of unemployment masks a far more complex pattern of the UK's unemployment experience. For many individuals unemployment is a short-lived affair. For others, the risk of repeated or prolonged periods of unemployment is high. Repeated or prolonged unemployment spells may reflect occupational choice or poor employability brought about by poor skills and/or repeated labour market exclusion. They may also reflect a lack of employment opportunities concentrated in specific geographical areas. Both facets amount to a significant detachment from work. They also contribute to recent growth in the level of non-working households and low pay. The differential risk of unemployment across UK regions and population sub-groups is well recognised. However, the extent to which residential location and individual heterogeneity contribute to the duration of unemployment is more difficult to discern. This paper investigates the impact of individual heterogeneity and regional influences on unemployment duration utilising cross-section microeconomic data drawn from a representative random survey of individual job seekers for the English County of Kent. These individual-level data are unique in that they provide information concerning the personal characteristics of job seekers, alongside direct observations of both their reservation wages and job search behaviour. The availability of such data is rare. To our knowledge, there is no existing study utilising such data at the regional level. This paper contributes to the empirical literature by analysing the extent to which individual heterogeneity and intra-regional variation in labour market opportunities impact upon the observed distribution of unemployment duration(s). In particular, the paper analyses the extent to which the duration of unemployment is determined by individual choice. This is an important issue for the formation and evaluation of policy. If individual choice is found to significantly influence the duration of unemployment then the efficacy of current microeconomic supply-side initiatives such as ?The New Deal? and other welfare to work policies is supported. The existence of regional influences, by contrast, advocates a more active role for macroeconomic demand-led management. It also supports a more integrated strategy for the implementation of urban and regional policy such as the recent creation of Frameworks for Regional Employment and Skills Action (FRESAs). Utilising an econometric model tied closely to job search theory, our results reveal that individual characteristics and related ?choice? variables' such as educational attainment, labour market mobility and job search behaviour exercise important impacts on the duration of unemployment. However, after controlling for such factors, there remain significant geographical variations. These results are robust for both males and females. Thus, the results provide new insights into the benefits of current policies aimed at increasing the employability of the unemployed.
Keywords: 330